Collectivization of smallholder farmers, strategic competition, and market performance: Experiences from two selected villages of West Bengal, India. Issue 3 (5th May 2022) - Bagchi, Niladri Sekhar; Mishra, Pulak; Behera, Bhagirath; Ratna Reddy, V.
Abstract: Given the structure and functioning of agricultural markets and the policies and institutional space, smallholder farmers in India often face the risks of strategic failures, which force them to either opt for distress selling, operate as fringe retailers or participate in the existing supply or value chains on given conditions. In this perspective, this paper examines if smallholder farmers' collectives can potentially strengthen their market position vis‐à‐vis other individual players and enable them to explore strategic options in a greater way. On the basis of the structure–conduct–performance theory and field experiences from two selected villages of West Bengal (India), the paper finds that the collectivization of smallholder farmers helps in exploring a larger set of strategic options for better outcomes. Further, the choice of the strategy set varies across the collectives depending on their composition, functioning, and resource endowments. Nevertheless, there is a possibility of strategic failures because of intra‐ as well as intercollective conflicts and competition from other players. The success in this regard would, therefore, depend on how the collectives democratically resolve such conflicts and develop capacity and capabilities to enhance their competitiveness for greater strategic success. Besides, addressing market imperfections through policy and institutional interventions would also be crucial.